PENGARUH KESADARAN PAJAK DAN KEPATUHAN PAJAK TERHADAP PEMBAYARAN PAJAK PERTAMBAHAN NILAI (PPN) PADA PELAKU USAHA APLIKASI ORDER MAKANAN ONLINE DI KECAMATAN TALANG KELAPA - Rahma Dwi Lestari; Lili Syafitri; Vhika Meiriasari (JURNAL ILMIAH EDUNOMIKA, 2026)
The growth of the digital economy in Indonesia has driven increased transactions through online food ordering apps, which has become a potential source of tax revenue. However, the level of awareness and compliance of business actors in fulfilling their tax obligations remains a challenge. This study aims to determine the effect of tax awareness and tax compliance on Value Added Tax (VAT) payments among online food ordering app business actors. The research method used was quantitative research with a survey approach. Primary data was obtained by distributing questionnaires to 97 business actors registered on online food ordering platforms. Data analysis used multiple linear regression with the help of SPSS version 27.0 software. The results show a significant effect of tax awareness on Value Added Tax (VAT) payments. Tax compliance also significantly influences Value Added Tax (VAT) payments. Simultaneously, tax awareness and tax compliance significantly influence Value Added Tax (VAT) payments. Keywords: Tax awareness, tax compliance, Value Added Tax (VAT) payments, Online Food Ordering Apps.